Implementation of K-Means Methods In Clustering Students Ability Levels in English Language - Cahyo Prianto; Rd Nuraini; Andi Tenri Wali (STMIK Budi Darma, 2019)
Nowadays, English extremely needs to be controlled, especially students, in communicating and reading also understanding literature written in English. In achieving mastery of English, the students, in this case, the students who are not majoring in English are given a common base subject of English. In Politeknik Indonesia, especially majoring in a Bachelor's Degree in Informatics Engineering, teaching English is using the direct method, to find out the results of teaching English within three semesters. Therefore, by doing this research for classifying the level of ability of students into three categories, they are Beginner, intermediate and advanced. The objective of the grouping is to determine how many students who have the capability level is low, medium and high so that the faculty can determine the average level of students' proficiency and the lecturers can intervene to conduct teaching in developing the students' knowledge of English. The classification used the K-Means clustering algorithm, which is one algorithm that classifies the same data on specific groups and different data in the other group. The results of this study by applying the k-means clustering method is the researchers can classify the students based on students' ability levels either they are beginner, intermediate or advanced.